Effects of Enterococcus faecalis UGRA10 and the enterocin AS-48 against the fish pathogen Lactococcus garvieae. Studies in vitro and in vivo. (February 2019) - Baños, Alberto; Ariza, Juan José; Nuñez, Cristina; Gil-Martínez, Lidia; García-López, J. David; Martínez-Bueno, Manuel; Valdivia, Eva
Abstract: The aim of this study was to evaluate the effects of Enterococcus faecalis UGRA10 and its enterocin AS-48 against the fish pathogen Lactococcus garvieae . The minimum bactericidal concentrations of AS-48 against L. garvieae CECT 5807, 5806, and 5274 were 15.62, 15.62, and 7.81 μg/ml respectively. In broth cultures, enterocin at 100, 50, and 25 μg/ml reduced 10 8  CFU/ml lactococci after 2, 5, and 10 h, respectively. In co-cultures of UGRA10/L . garvieae at a 1/10 CFU/ml ratio, lactococci were eliminated after 24 h. Studies on UGRA10 biosafety and AS-48 toxicity in R1 cells and in rainbow trout have shown a lack of adverse effects from both the strain and bacteriocin. Trout challenged with L. garvieae and UGRA10 administered in diet 30 days before infection had a cumulative survival rate of 50% compared with 0% for control fish. Trout inoculated with the pathogen and treated by regular dipping in AS-48 baths had a survival rate of 60% after 20 days compared with that of untreated fish (0%). These results indicate the protective effect of the UGRA10 strain and the bacteriocin AS-48 against L. garvieae and the potential of these natural products as alternatives to antibiotics for controlling diseases in aquaculture. Highlights: Effects of UGRA10 strain and bacterocin AS-48 on Lactococcus garvieae were tested. Neither Enterococcus faecalis UGRA10 or AS-48 showed adverse effect on trout. UGRA10 strain administered in diet protected trout against L. garvieae infection. Dipping in AS-48 baths protected trout against L. garvieae infection.